Comparison of the pharmacokinetics of two formulations of hydroxyethyl starch in healthy horses. Issue 3 (21st September 2016) - Epstein, K. L.; Bergren, A.; Nie, B.; Arnold, R. D.; Brainard, B. M.
Abstract : A lower molecular weight and molar substitution formulation (130/0.4) of hydroxyethyl starch solution has been shown to have a more sustained effect on COP and similar hemodynamic effects as a higher molecular weight and molar substitution formulation (600/0.75) in healthy horses. In humans, these pharmacodynamic characteristics are coupled with more rapid clearance and decreased adverse coagulation effects and accumulation. The objective of this study was to determine and compare the pharmacokinetics of these two formulations in horses. Eight healthy horses were given a 10 mL/kg bolus of each formulation (600/0.75 and 130/0.4) of hydroxyethyl starch solution in a randomized crossover design. Blood was collected, and plasma was harvested for plasma levels over 24 h. Pharmacokinetic parameters for each horse were estimated from a noncompartmental analysis. Treatment with 600/0.75 resulted in a higher initial plasma concentration ( C 0 ), systemic half‐life ( t 1/2 ), and overall drug exposure (AUC0–inf ) in addition to decreased elimination rate ( β ), volume of distribution (Vd), and clearance (CL), compared to treatment with 130/0.4 ( P  < 0.001). The pharmacokinetic findings combined with previous pharmacodynamics findings suggest that 130/0.4 can provide similar benefits to 600/0.75 with a lower risk of accumulation in the circulation.